Puerto Rico : the trials of the oldest colony in the world - Trías Monge, José (Yale University Press, 1997)
Jose Trias Monge first describes the Spanish rule over Puerto Rico and then traces the impact of American colonial policies there, comparing them with those in the Pacific and the British, French, and Dutch experiences in the Caribbean. He argues that the large amounts of money the United States has given to Puerto Rico have not been productive: not only has the island become frightfully dependent on United States munificence but more than 60 percent of Puerto Rican families still live below the poverty line. Politically, the situation is even worse.